Skin and Mucosal Human Papillomavirus Seroprevalence in Persons with Fanconi Anemia - Katzenellenbogen, Rachel A. (Clin Vaccine Immunol, 2015)
Persons with Fanconi anemia (FA) are at risk for human papillomavirus (HPV)-associated cancers; however, their natural HPV exposure and infection rates are unknown as is the adequacy with which they mount antibodies to HPV vaccination. This study aimed to determine, in 62 persons with FA, the seroprevalence of skin and mucosal HPV types, the seroprevalence in individuals self-reporting a history of HPV vaccination, and the factors associated with HPV seropositivity. A bead Luminex assay was used to determine seropositivity for HPV1, -2, and -4 (low-risk skin), -6 and -11 (low-risk mucosal, included in one HPV vaccine), -16 and -18 (high-risk mucosal, included in both HPV vaccines), and -52 and -58 (high-risk mucosal). Health- and behavior-related questionnaires were completed. Type-specific seroprevalence estimates and participant characteristics associated with seroprevalence were calculated; 48% reported HPV vaccination. Type-specific seropositivity in unvaccinated persons ranged from 7 to 21% for skin HPV types and 7 to 38% for mucosal HPV types. Among the unvaccinated participants, adults versus children demonstrated increased HPV1, -6, -16, and -58 seroprevalence of 45% versus 6%, 64% versus 22%, 64% versus 17%, and 36% versus 0%, respectively (all P < 0.05). The vaccinated participants versus the nonvaccinated participants demonstrated increased seroprevalence of HPV6, -11, -16, and -18 of 92% versus 38%, 92% versus 24%, 96% versus 34%, and 75% versus 7%, respectively (all P < 0.0001). Our data demonstrate that the unvaccinated participants had serologic evidence of prior skin and mucosal HPV infections and that seroprevalence increased among adults; in self-reported vaccinees, seroprevalence of HPV vaccine types was 75 to 96%.